2022
DOI: 10.1029/2021gl096513
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Impacts on the Patagonian Shelf Break Front

Abstract: During the past decades climate change has been reported to produce an intensification of the transports of western boundary currents and a poleward shift of the major subtropical ocean gyres (Wu et al., 2012;Yang et al., 2016Yang et al., , 2020. The subtropical gyre of the South Atlantic Ocean and its western boundary current-the Brazil Current (BC)-has shifted at a rate of 0.11°/decade (Yang et al., 2016(Yang et al., , 2020. The poleward shift and intensification of the BC has caused a warming of the adjacen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 39 publications
10
12
0
Order By: Relevance
“…Our results (see R7 and R2 in Table 1) are consistent with recent studies reporting a warming trend of 0.4° decade -1 in the Brazil-Malvinas Confluence and the SBF (e.g. Franco et al, 2020Franco et al, , 2022 as well as in the San Matías and Nuevo Gulfs (Williams and Nocera, 2023). Also, a higher water temperature associated with global warming is predicted over the shelf where the heat exchange between the sea and the atmosphere is strong (Leyba et al, 2019), and this is in agreement with the most pronounced warming trend found in our study.…”
Section: Environmental Phytoplankton Biomass and Phenology Trends In ...supporting
confidence: 92%
See 3 more Smart Citations
“…Our results (see R7 and R2 in Table 1) are consistent with recent studies reporting a warming trend of 0.4° decade -1 in the Brazil-Malvinas Confluence and the SBF (e.g. Franco et al, 2020Franco et al, , 2022 as well as in the San Matías and Nuevo Gulfs (Williams and Nocera, 2023). Also, a higher water temperature associated with global warming is predicted over the shelf where the heat exchange between the sea and the atmosphere is strong (Leyba et al, 2019), and this is in agreement with the most pronounced warming trend found in our study.…”
Section: Environmental Phytoplankton Biomass and Phenology Trends In ...supporting
confidence: 92%
“…The depth and properties of the MLD depend on ocean-atmosphere exchanges which are strongly influenced by climate variability (Sallée et al, 2010). Our results indicate consistent shallowing of the MLD (Table 1) and agree with a previous study which address a shoaling trend of the MLD in the Patagonian Shelf (Franco et al, 2023;Williams and Nocera, 2023), with the highest values in the north-western portion of the mid-shelf and the shelf-break (Franco et al, 2022), also in line with the highest trend find in R7 of this study. In the Patagonian shelf the MLD depends mainly on the thermal stratification (Signorini et al, 2006); thus, the increase in SST due to global warming is expected to produce longer periods of shallower MLD (typical of spring and summer), resulting in the negative observed trend.…”
Section: Environmental Phytoplankton Biomass and Phenology Trends In ...supporting
confidence: 92%
See 2 more Smart Citations
“…Such a diet switch has been recorded in the North Pacific blackfooted albatross Phoebastria nigripes that increased discard consumption during a year of record-high SST (Conners et al, 2018) and also in the Benguela system where Cape gannets Morus capensis increased discard consumption when natural prey were scarce (Tew Kai et al, 2013;Cohen et al, 2014). In light of predicted rising sea surface temperatures as a result of climate change (IPCC, 2019;Franco et al, 2022), this pattern warrants particular attention in the context of conservation. The impact of environmental and fishery effects on prey availability are likely to be highly complex and systemspecific, however (Inchausti et al, 2003;Rolland et al, 2008;Wren et al, 2019).…”
Section: Relationship Between Breeding Success Discards and Foraging ...mentioning
confidence: 88%